Analysis of Venture Capital Investment for Financing The Development of The Palm Oil Industry in Indonesia for Private Companies - Yitro, Salvatore; Sari, Mustika; Saroji, Gunawan (CSID Journal of Infrastructure Development, 2026)
Indonesia is the world's largest crude palm oil (CPO) producer, accounting for 58.04% of global output from 2018 to 2022 and generating between USD 18.2 billion and USD 28.95 billion in annual foreign exchange earnings from 2016 to 2021. The downstream sector, however, remains largely controlled by foreign markets, and private companies face restricted access to conventional bank financing due to negative campaigns against Indonesian palm oil in European markets. No prior study has examined the financial feasibility of venture capital as a financing mechanism for integrated downstream palm oil development by private companies in Indonesia. This study analysed that feasibility using the Discounted Cash Flow (DCF) method, applied to a case study of CS COMPANY, an integrated downstream facility comprising a refinery, fractionation plant, biodiesel plant, oleochemical plant, and CPKO refining and hydrogenation plant, over a 10-year investment period in accordance with OJK regulations. The WACC was 10.59%, benchmarked against specialty chemicals peers in Asian capital markets. The NPV was IDR 238,154,411,444, indicating a positive return above the cost of capital. The IRR was 12.07%, exceeding the WACC and confirming financial feasibility. Payback period analysis confirmed capital recovery within the 10-year investment period. Sensitivity analysis showed the project remains feasible under conservative assumptions. The projected market value at divestment was IDR 2,025,884,135,004, with a 30% DLOM applied per OJK Regulation Number 35/POJK.04/2020. These results confirm that venture capital is a financially viable and legally structured financing instrument for downstream palm oil development in Indonesia. The study contributes a replicable DCF framework calibrated to POJK regulations for use by investors and companies evaluating similar structures. Future research should examine alternative venture capital schemes, multi-project comparisons, and non-financial risk integration.